2013
DOI: 10.1001/jamapediatrics.2013.1100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volunteering on Risk Factors for Cardiovascular Disease in Adolescents

Abstract: Importance:The idea that individuals who help others incur health benefits themselves suggests a novel approach to improving health while simultaneously promoting greater civic orientation in our society. The present study is the first experimental trial, to our knowledge, of whether regular volunteering can reduce cardiovascular risk factors in adolescents.Objective: To test a novel intervention that assigned adolescents to volunteer with elementary school-aged children as a means of improving adolescents' ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 38 publications
5
107
0
2
Order By: Relevance
“…• Improved affect 16 • Improvement in self-rated health 22,23,28,29,33,34,49,[51][52][53] • Greater longevity [10][11][12][13][14]24,33,35,36,[54][55][56] • Improved ability to carry out activities of daily living 22,24,33,52 • Better health coping mechanisms 4 • Reduced cardiovascular risk factors: lower cholesterol, interleukin 6, and body mass index 1 • Less hypertension 57 • Adoption of healthy lifestyles such as disease prevention, 39 increased physical activity, 58 and responsible amounts of drinking 59 • Lower incidence of frailty in later life 60 • Fewer hospitalizations 29 • Improved pain management 46 …”
Section: Physical Health Benefitsmentioning
confidence: 99%
“…• Improved affect 16 • Improvement in self-rated health 22,23,28,29,33,34,49,[51][52][53] • Greater longevity [10][11][12][13][14]24,33,35,36,[54][55][56] • Improved ability to carry out activities of daily living 22,24,33,52 • Better health coping mechanisms 4 • Reduced cardiovascular risk factors: lower cholesterol, interleukin 6, and body mass index 1 • Less hypertension 57 • Adoption of healthy lifestyles such as disease prevention, 39 increased physical activity, 58 and responsible amounts of drinking 59 • Lower incidence of frailty in later life 60 • Fewer hospitalizations 29 • Improved pain management 46 …”
Section: Physical Health Benefitsmentioning
confidence: 99%
“…Volunteers have lower c-reactive protein levels compared to non-volunteers (Konrath 2013). This effect was confirmed in an experimental study that found that adolescents who were randomly assigned to a four-month volunteering program had marginally lower inflammatory biomarkers (c-reactive protein and interleukin 6) than waitlist control-group participants (Schreier 2012;Schreier et al 2013). They also had lower levels of cholesterol and a lower BMI.…”
Section: (F) Basic Physiological Measuresmentioning
confidence: 77%
“…Although there have been studies examining the effect of other prosocial behaviors on cortisol levels (e.g., Field et al 1998;Smith et al 2009), there is only one known study examining cortisol in relation to volunteering. This experimental study found that a four-month volunteering program had no effect on adolescents' cortisol levels compared to a waitlist control condition (Schreier et al 2013;Schreier 2012). More research is needed to examine the relationship between cortisol and volunteering.…”
Section: (C) Cortisolmentioning
confidence: 89%
“…[42][43][44] In general, it is well known that increased systemic inflammation is a risk factor for increase in chronic diseases and reduction in life span. [55][56][57][58] The practice of these health principles since early childhood may have afforded the centenarians and seniors enhanced ability to counter the effects of High family social strain associated with significant increase in IL-6 and fibrinogen and with overall inflammation burden (index variable created from all 5 markers) Kiecolt-Glaser et al, 36 2005 IL-6 and TNF-α Hostile marital interactions associated with stronger acute increase in proinflammatory markers (IL-6 and TNF-α) Helping hand Schreier et al, 37 2013 IL-6 Volunteer time associated with significant decrease of IL-6, cholesterol, and BMI measurements Fuligni et al, 38 2007 IL-6 and CRP Greater sense of fulfillment in helping others associated with significantly lower IL-6 and CRP levels Hopeful intrinsic drive Puig-Perez et al, 39,40 2017, 2015 Cortisol Optimism related to significantly lower daily cortisol levels and faster cortisol recovery after stressful experiences Roy et al, 41 2010 IL-6 and CRP Optimism significantly linked with lower IL-6; pessimism significantly related to higher IL-6 and CRP levels Kinetic life Hopps et al, 42 2011 CRP, IL-6, IL-1β, and TNF-α Physical activity associated with significant decrease in CRP, IL-6, IL-1β, and TNF-α levels Autenrieth et al, 43 2009 CRP and IL-6 Physical work and transportation (cycling/walking) to work associated with lower levels of CRP and IL-6 Reuben et al, 44 2003 CRP House/yard work associated with significantly lower risk of elevated CRP levels Nature engagement Li, 45 2010 Cortisol Forest outing trips associated with significant decrease in salivary cortisol levels Roe et al, 46 2013 Cortisol Higher green space in urban city spaces associated with significant decreased stress and cortisol levels Guillot et al, 47 2010 CRP Vitamin D (major source is sunlight exposure) associated with significant decrease in CRP levels Resting reset Okun et al, 48 2011 IL-6 and TNF-α Routine sleep practices associated with significantly lower plasma levels of proinflammatory markers Lin et al, 49 2012 IL-6 Leisure mental activities, including reading, attending lectures, and playing cards, were associated with significantly lower levels of IL-6 Simple foods Nettleton et al, 50 2006 CRP, IL-6 Whole grains, fruits, nuts, and green leafy vegetables inversely associated with significantly lower CRP, IL-6, and homocysteine levels Hodgson et al, …”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%